Properties of a homogeneous C-lobe prepared by introduction of a TEV cleavage site between the lobes of human transferrin - Steere, Ashley N. (2010)
Essential to iron transport and delivery, human serum transferrin (hTF) is a bilobal glycoprotein capable of reversibly binding one ferric ion in each lobe (the N- and C-lobes). A complete description of iron release from hTF, as well as insight into the physiological significance of the bilobal structure, demands characterization of the isolated lobes. Although production of large amounts of isolated N-lobe and full-length hTF has been well documented, attempts to produce the C-lobe (by recombinant and/or proteolytic approaches) have met with more limited success. Our new strategy involves replacing the hepta-peptide, PEAPTDE (comprising the bridge between the lobes) with the sequence ENLYFQ/G in a His-tagged non-glycosylated monoferric hTF construct, designated Fe(C)hTF. The new bridge sequence of this construct, designated Fe(C)TEV hTF, is readily cleaved by the tobacco etch virus (TEV) protease yielding non-glycosylated C-lobe. Following nickel column chromatography (to remove the N-lobe and the TEV protease which are both His tagged), the homogeneity of the C-lobe has been confirmed by mass spectroscopy. Differing reactivity with a monoclonal antibody specific to the C-lobe indicates that introduction of the TEV cleavage site into the bridge alters its conformation. The spectral and kinetic properties of the isolated C-lobe differ significantly from those of the isolated N-lobe.